Unveiling bioactive compounds in kola nut seeds: GC-MS identification and computational analysis for anticancer potential - Alshehri, Azzah; Bahaffi, Saleh; Rehan, Mohd; Suhail, Mohd; Al-Asmari, Ahmed I.; Youssef, Diaa T. A.; Khedr, Alaa; Zughaibi, Torki (Frontiers in Nutrition, 2026)
IntroductionCancer continues to pose a critical global health challenge, with conventional therapies often limited by efficacy and adverse side effects. In search of safer and more effective treatments, medicinal plants offer a treasure trove of bioactive compounds with therapeutic potential. Kola nut (Cola spp.), a tropical evergreen native to the African rainforests, has long been valued in traditional medicine and as a natural stimulant.MethodsThis study explores the anticancer potential of kola nut seeds extract by first identifying its chemical constituents through gas chromatography–mass spectrometry (GC-MS), followed by molecular docking of selected compounds against the cancer-associated target PI3Kα. A methanolic extract was fractionated using column chromatography, yielding nine distinct fractions. The first four fractions were analyzed directly by GC-MS, while the remaining five were derivatized (silylated) prior to analysis.Results and discussionA total of 78 diverse compounds were identified, spanning alkaloids, flavonoids, fatty acids, and carbohydrates. From these, 15 bioactive compounds, including scopolin, picropodophyllin, catechin, yohimbine, squalene, campesterin, epicatechin, stigmasterol, p-coumaric acid, quinoline, methyl linoleate, methyl oleate, DTB-spdione, theobromine, and caffeine, were shortlisted for in silico docking studies. Molecular docking of 15 kola nut bioactive compounds against PI3Kα revealed that squalene, campesterin, epicatechin, yohimbine, and scopolin exhibited favorable binding energies, engaging key residues. Fatty-acid esters showed moderate binding, while small compounds such as theobromine and caffeine displayed weak interactions. Overall, these findings highlight the potential of kola nut phytochemicals as scaffolds for PI3Kα-targeted drug development. Based on enhanced fractionations, our study provides an expanded chemical profile of kola nut seeds and suggests that selected phytochemicals may serve as promising candidates for anticancer drug development. Further experimental validation is warranted to translate these insights into therapeutic applications.